Office-Based Procedures in the Management of Hemorrhoidal Disease: Rubber Band Ligation versus Sclerotherapy - Systematic Review and Meta-Analysis - Salgueiro,Paulo (2022)
Abstract Introduction: The most frequently used office-based procedures in hemorrhoidal disease (HD) are rubber band ligation (RBL) and sclerotherapy. Few studies have been published comparing the various types of instrumental therapy. The aim of this systematic review and meta-analysis was to compare the efficacy and safety of sclerotherapy and RBL. Methods: Three online databases were searched. Efficacy (control of symptoms, prolapse, bleeding and pain, patients’ satisfaction, and disease recurrence) and safety (complications, such as pain and bleeding) were the assessed outcomes. Pooled relative risks (RR) were computed for each outcome using a random-effects model, and heterogeneity was assessed by Cochran’s Q test and I2. Results: Six RCTs and three cohort studies were included. Control of prolapse and bleeding was significantly higher with RBL (93.1% RBL vs. 66.4% sclerotherapy, RR 1.34, 95% CI 1.12-1.60 and 89.1% RBL vs. 78.7% SCL, RR 1.17, 95% CI 1.02-1.34, respectively). Both techniques had similar results in terms of pain relief, overall control of symptoms, and risk of recurrence at 3 months. Although patient satisfaction was significantly higher with RBL (77.8% RBL vs. 46.7% sclerotherapy, RR 1.59, 95% CI 1.01-2.50), post-procedural pain was significantly higher with this technique (24% RBL vs. 14% sclerotherapy, RR 1.74, 95% CI 1.32-2.28). There was no significant difference regarding post-procedure bleeding (11.1% RBL vs. 8.7% sclerotherapy, RR 1.29, 95% CI 0.86-1.94). In the subgroup analysis, according to the HD grade, post-procedure pain was higher with RBL only in HD grade II (vs. HD grade I-III). Conclusions: RBL performs better than sclerotherapy in controlling HD symptoms, specifically prolapse and bleeding, although post-procedural pain is a frequent complication. Recurrence is similar with both procedures. While waiting for the publication of results with sclerotherapy with new sclerosants, RBL remains the office-based treatment of choice in HD.